2022
DOI: 10.3389/fcell.2021.787356
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Promotes Exosome Biogenesis and Release via Modulating Rabs and miR-192 Expression in Human Hepatocytes

Abstract: Exosomes are membrane vesicles released by various cell types into the extracellular space under different conditions including alcohol exposure. Exosomes are involved in intercellular communication and as mediators of various diseases. Alcohol use causes oxidative stress that promotes exosome secretion. Here, we elucidated the effects of alcohol on exosome biogenesis and secretion using human hepatocytes. We found that alcohol treatment induces the expression of genes involved in various steps of exosome form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…In our previous studies, we reported that ethanol-induced EV miRNAs such as miR-140-3p could mediate aberrant astroglial differentiation, while suppressing neuronal and oligodendroglial lineage markers [ 23 ], and retroviral-like proteins present in EVs, like PEG10 and PNMA2, could lead to apoptosis-resistance [ 22 ]. Moreover, EV reprogramming has been implicated in microglial activation and inflammation-mediated loss of developing hypothalamic neurons [ 45 ], and in the pathogenesis of alcohol-associated liver disease [ 46 , 47 ], suggesting that EVs are a component of a broader cellular and tissue sensitivity to this common perturbagen. These observations advance a novel possibility that EVs secreted by NSCs may reflect NSC reprogramming by the environment and, consequently, transfer the effects of a perturbagen between cells, thereby contributing to the spread and persistence of deleterious effects within the neurogenic niche.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we reported that ethanol-induced EV miRNAs such as miR-140-3p could mediate aberrant astroglial differentiation, while suppressing neuronal and oligodendroglial lineage markers [ 23 ], and retroviral-like proteins present in EVs, like PEG10 and PNMA2, could lead to apoptosis-resistance [ 22 ]. Moreover, EV reprogramming has been implicated in microglial activation and inflammation-mediated loss of developing hypothalamic neurons [ 45 ], and in the pathogenesis of alcohol-associated liver disease [ 46 , 47 ], suggesting that EVs are a component of a broader cellular and tissue sensitivity to this common perturbagen. These observations advance a novel possibility that EVs secreted by NSCs may reflect NSC reprogramming by the environment and, consequently, transfer the effects of a perturbagen between cells, thereby contributing to the spread and persistence of deleterious effects within the neurogenic niche.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that VAMP5 was associated with promotion of exosome secretion. Bala et al found that VAMP5 was increased at the mRNA level and correlated with increased exosome secretion in alcohol-treated cells and in the liver of patients with Alcohol-associated liver disease (ALD) [23]. Although the role of VAMP5 in NAFLD and HCC has not been reported, while it was showed that VAMP5 rs1254900 was signi cantly associated with colorectal cancer [24].…”
Section: Discussionmentioning
confidence: 99%
“…277 Alcohol consumption substantially increases EV biogenesis and secretion from liver cells and also affects their contents. 278,279 The number of circulating EVs in plasma samples of acute alcoholic hepatitis patients was found to be higher compared with EV levels in healthy donors. 280 EV content comprises DNA, protein, lipids cargo, metabolites, mRNA, and noncoding RNA.…”
Section: Extracellular Vesicles (Evs) As Diagnostic Toolsmentioning
confidence: 97%